PENGATURAN PENGGUNAAN GANJA SEBAGAI BAHAN BAKU PRODUKSI OBAT - Marainaya, Riviera Constine; Mangesti, Yovita Arie (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Marijuana is used for medicinal purposes because it contains several chemical compounds that can cure various diseases. It was explained that cannabis is included in a type of narcotics class 1 because it contains tetrahydrocannabinol (THC), in the Narcotics Law that the term "consuming" is not explained. Some of the articles of the Narcotics Law only explain or include things such as: using, storing, possessing, providing, controlling, offering, intermediary, trading, receiving, or handing over. This research is normative legal research with a statutory and conceptual approach by finding arrangements for the use of cannabis as a raw material for drug production, and what are the rules or legal consequences if it violates the provisions against the use of cannabis as a raw material for drug production. The reason is that until now there are still many Indonesian people who use cannabis illegally as an alternative treatment or use traditionally processed cannabis